2000
DOI: 10.1063/1.1317538
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the emission characteristics of light emitting diodes by surface plasmons and surface waveguide modes

Abstract: In this letter, the influence of metal films and dielectric waveguides on the radiation characteristics of light emitting diodes (LEDs) is investigated. Cross and hexagonal surface grating structures are used to excite surface plasmons and waveguide modes in these media. A beam divergence as small as 17° is achieved for a hexagonal grating coated with a 40 nm Ag film. The maximum quantum efficiency is found for a hexagonal grating with a 10-nm-thick Au film and a 250-nm-thick dielectric layer. The optical powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…Gianordoli et al optimized the emission characterization of GaAs-based LED by SP. 25 Vuckovic et al reported the SP enhanced LED analyzing by both theoretically and experimentally. 26 Thus, great attention has been focused on SP enhanced emission.…”
Section: -9mentioning
confidence: 99%
“…Gianordoli et al optimized the emission characterization of GaAs-based LED by SP. 25 Vuckovic et al reported the SP enhanced LED analyzing by both theoretically and experimentally. 26 Thus, great attention has been focused on SP enhanced emission.…”
Section: -9mentioning
confidence: 99%
“…3 Recently, we have reported a method for enhancing the light emission efficiency from InGaN QWs by controlling the energy transfer between QW emitters and surface plasmons ͑SPs͒. 4 The idea of SP enhanced light emission was previously described [5][6][7][8][9][10][11][12][13][14][15] and efficient SPenhanced visible light emission has been demonstrated. 4 Moreover, the enhancement of an emission rate is also very important for the development of communication technology and optical computing.…”
mentioning
confidence: 99%
“…Typically, when light emitted from multi-quantum wells of LED interacts with a metallic layer, a surface plasmon mode will be formed. This surface plasmon mode increases the density of states and spontaneous emission rate (Gianordoli et al, 2000;Hecker et al, 1999;Vuckovic et al, 2000), and thus helps to improve coupling from the multi-quantum wells (Neogi et al, 2002). There have been reports that successfully demonstrated enhancement in InGaN quantum well emission by means of enhancement of Purcell factor with surface plasmons making use of a metal film on top of an LED (Okamoto et al, 2004).…”
Section: Surface Plasmonmentioning
confidence: 99%